Genotyping of Escherichia Coli Isolated from Diarrhea Cases in Children under Five Years of age Using the PFGE Method (Bangladesh Journal of Medical Science, 2023)
Twenty –five isolates of Escherichia coli isolated from cases of diarrhea in children under five years of age were obtained, characterized by Extensively Drug-Resistant(XDR) resistance patterns, and sensitivity screening of isolates was performed.E7 isolates were resistant to 4 groups of antibiotics and E5 - E13 - E14 - E17 - E18 - E20 - E47 - E46 - E42 - E31 - E26 isolates resistant to 5 groups of antibiotics and 48E isolate resistance to 6 groups of antibiotics and consisting of E2 E38 - E36 - E34 - E28 - E16 - E10isolates showed resistance to 7 groups of antibiotics, and E41 - E24 - E19 - E9 –E1 isolates resistance to 8 groups of antibiotics. The genotyping of 25 E.coliisolates was carried out by Pulsed-field Gel Electrophoresis (PFGE) using restriction endonucleases (Xbal) which belong to different phylogenetic groups, were as group A, group B2, group D (2/25 and 8%) group C (4/25 and 16%), group F (3/25 and 12%), group E (12/25 and 48%). The genetic convergence rate of isolates is 83%, and this is due to the similarity in genetic content, the source of isolation, and the place of isolation itself.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.18-24